2016
DOI: 10.5354/0719-5370.2016.41215
|View full text |Cite
|
Sign up to set email alerts
|

Un análisis comparativo del comportamiento diferencial de los glaciares en los Andes Tropicales usando teledetección

Abstract: In this research paper, we analysed the behaviour of Tropical Andean glaciers in a changing climate. We used multi-source satellite images as well as meteorological datasets to achieve this objective. Representative glaciers in four different climatic zones, namely the inner tropics, northern wet outer tropics, southern wet outer tropics and dry outer tropics, were considered in this study. Changes in annual maximum snowline during 1985 -2015 and also the decadal changes in the area between 1975 and 2015 of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Northern Wet Outer Tropics, Southern Wet Outer Tropics, Dry Outer Tropics, and Inner Tropics (Figure 1). [39] and their climatic classification based on Sagredo and Lowell [27,40,41].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Northern Wet Outer Tropics, Southern Wet Outer Tropics, Dry Outer Tropics, and Inner Tropics (Figure 1). [39] and their climatic classification based on Sagredo and Lowell [27,40,41].…”
Section: Study Areamentioning
confidence: 99%
“…In recent years, the availability, accessibility, and temporal and spatial continuity of satellite data (such as Landsat and Sentinel) [25][26][27][28] and the development of cloud computing platforms, such as Google Earth Engine (GEE) [29], have created an opportunity to map the historical evolution of land cover change, such as water bodies and glaciers [16,18,21,26,[30][31][32][33][34][35][36]. Despite the progress made in recent years in the assessment of glacier areas, there are still many cases in which the automatic delimitation of glacier boundaries in satellite images is complex, error prone, or time consuming [13,20,37].…”
Section: Introductionmentioning
confidence: 99%
“…Tropical glaciers in the Andes, particularly in the eastern cordilleras of Peru and Bolivia, were extensively studied in recent years due to their functionality as climate proxies (Vuille et al, 2008a(Vuille et al, , 2008bVeettil et al, 2016aVeettil et al, , 2016b and freshwater resource during dry season (Soruco et al, 2015). Based on the recent Randolph Glacier Inventory (RGI version 5.0), more than 99% of the tropical glaciers of the world are situated in the Andes and nearly 70% of the tropical Andean glaciers are in Peru (Pfeffer et al, 2014), distributed in 20 distinct glacierized mountain ranges (cordilleras) (Morales-Arnao, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies on the Andes have confirmed that climatic variables are directly or indirectly linked to global indices [74,[110][111][112][113][114][115][116][117][118][119]. The study correlated greenness with various global climate indices, among which the North Atlantic Oscillation (NAO) had the highest Pearson coefficients.…”
Section: Ndvi Analysis-global Climate Indicesmentioning
confidence: 93%
“…NDVI is an indicator of vegetation response that has been used in multiple ecosystem studies [44,[72][73][74][75]. NDVI is sensitive to chlorophyll in leaves and is calculated in terms of reflectance at red and near-infrared wavelengths, according to Equation (1) [13].…”
Section: Ndvi Datasetmentioning
confidence: 99%